THE ECONOMIC COMPONENTS OF THE FORMATION OF GEORGIAN FEDERALISM - GLONTI, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2005)
An analysis of the formation of federative relations in Georgia shows us there is no clear conception of their development prospects. The inconsistency of the transformations in this area is manifested primarily in the ambiguity of property relations, the contradictions in the inter-budgetary sphere, and so on. But these facts are not the cause, rather they are the effect of the overall low level of theoretical development of a corresponding state structure model. All of these problems have led to a situation where the formation of socioeconomic components is being confused with the regulatory attributes of a federative state. After all, there is a qualitative difference between them, and history shows how underestimating them leads to serious negative consequences. The methodological meaning of these differences is as follows. A federation arises when this form of state is recognized as beneficial to society, in other words, when it meets society’s interests. So, a vital prerequisite of the federalization process is achieving a certain qualitative level of social relations throughout the entire system, including in the socioeconomic, ethnopolitical, regulatory, and other spheres. From this it follows that even though the constitution and other legislative acts of a state may declare it a federation for all external intents and purposes, in the historical respect, a different cause-and-effect relation comes into play here. Its gist lies in the fact that, first, socioeconomic, political, and other prerequisites of the formation of such a state come to maturity, then a corresponding interest forms among the population, and only after that does the law register the fact that the fundamental principles of federative relations have been created. If we uphold the viewpoint that the appearance of a federative state is largely related to the drawing up and constitutional enforcement of regulatory instruments and institutions for regulating federative relations, it is logical to acknowledge that the motive behind choosing this form of statehood is not the interest of society or citizens, but the desire of lawyers to find ways to substantiate the political demands of certain interest groups. This scenario was played out, for example, in the Soviet Union. But the collapse of Soviet, as well as of Yugoslavian and Czechoslovakian, “federalism” showed the flimsiness of the formal federations that arise out of such choices.